2009
DOI: 10.1177/112067210901900616
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory mediators and posterior segment involvement in ocular Behçet disease

Abstract: This study demonstrated that increased serum levels of inflammatory mediators including IL-6, IL-8, TNF-alpha, VEGF, and MDA were possibly involved in the development of posterior uveitis in BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…A recent study demonstrated that serum levels of interleukin (IL)-6, IL-8, TNF-a, vascular endothelial growth factor, and malondialdehyde were significantly higher in patients with active ocular BD than in those with inactive ocular BD, indicating that increased serum levels of inflammatory mediators are possibly involved in the development of uveitis in BD. 44 Bardak and Aridogan 24 reported that serum levels of immunoglobulin (Ig) A, complement (C) 3, C4, IL-6, IL-8, and TNF-a were higher during the active uveitis period of BD patients than those in the convalescence period of the same patients and in those of healthy controls, suggesting that Ig A, C3, C4, IL-6, IL-8, and TNF-a-mediated mechanisms might be responsible for ocular lesions in BD. Similarly, sTREM-1 may be involved in the pathogenesis of ocular lesions in BD.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study demonstrated that serum levels of interleukin (IL)-6, IL-8, TNF-a, vascular endothelial growth factor, and malondialdehyde were significantly higher in patients with active ocular BD than in those with inactive ocular BD, indicating that increased serum levels of inflammatory mediators are possibly involved in the development of uveitis in BD. 44 Bardak and Aridogan 24 reported that serum levels of immunoglobulin (Ig) A, complement (C) 3, C4, IL-6, IL-8, and TNF-a were higher during the active uveitis period of BD patients than those in the convalescence period of the same patients and in those of healthy controls, suggesting that Ig A, C3, C4, IL-6, IL-8, and TNF-a-mediated mechanisms might be responsible for ocular lesions in BD. Similarly, sTREM-1 may be involved in the pathogenesis of ocular lesions in BD.…”
Section: Discussionmentioning
confidence: 97%
“…Clinical studies TNF-α levels are elevated both in the serum and aqueous humor of patients with uveitis, and these increased levels correlate with disease status. 2,101,117 T-cells extracted from the aqueous humor of non-infectious uveitis patients spontaneously produce significant levels of TNF-α. 115 As previously seen in experimental models, persistent production of TNF-α is associated with tissue damage via reactive oxygen species, promotion of angiogenesis, and breakdown of the blood-ocular barrier.…”
Section: Role Of Tnf-α In Uveitismentioning
confidence: 99%
“…Fecal calprotectin (FC) were demonstrated to be significantly elevated in intestinal BD in several studies [226][227][228], and interestingly Özşeker et al demonstrated high fecal FC levels in asymptomatic but endoscopically proven BD patients with intestinal involvement [226]. Vascular endothelial growth factor (VEGF) levels have been observed in BD patients, particularly in active BD [229][230][231][232]. Several studies provided evidence for the increased levels of markers for endothelial activation or dysfunction such as vascular and intercellular adhesion molecules VCAM1, ICAM1, Selectins, and YKL40 in BD [233][234][235][236][237][238].…”
Section: Other Possible Markersmentioning
confidence: 99%